(3GdTGajI aj GdJUQjas - (3GdeGdcj GdeUQj GdCSfhj, CHh YeQh, GHf GdMGLH, LeGd GdOjf, YKeGf Hf YeQ Hf CHj HcQ, J(B646(3g`s ((3eOQSI TgQRGOs)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejfhHYO abO SCdfj ef dG hdG jSYfj eNGdaJgCf GdMb HebOeJj aj GdEYQGH ebOeI aj GdJUQja Ydi fMhgG hebOeI aj GdNW aCLHJgs
(3BNQgG (B:s
(3hGhG CeG GdMQha ade jcJH efgG HGdjGA hZjQgG hEdi hYdi hMJi hGddg CYdes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: 4 / 211s
(3eYLe GdeDdajf(B: 2 / 366s
(3cTa GdXfhf(B: 2 / 1020s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdUQas